Analysis of Volatile Components and Flavor Characteristics of Zaolu from Different Origins - Jiayi HUANG; Yuke PENG; Wenxuan TIAN; Yanzhe CHENG; Zitian CHEN; Yaning CHANG (Shipin gongye ke-ji)
Zaolu, a distinctive regional fermented delicacy, was renowned for its pronounced aroma and rich, mellow flavor. A deeper comprehension of the olfactory and gustatory profiles of Zaolu variants was facilitated by analyzing their flavor variances, thereby enhancing product quality. Four geographically distinct Zaolu samples were scrutinized in this research, with gas chromatography-mass spectrometry (GC-MS) employed to identify and quantify the predominant volatile flavor compounds. Flavor disparities were investigated by integrating the electronic nose, while the taste intensity was assessed through electronic tongue modeling and sensory analysis. Ultimately, the flavor characteristics and signature components intrinsic to the diverse origins of Zaolu were elucidated. The flavor characteristics and signature components of Zaolu from diverse origins were revealed by this comprehensive approach. Results showed that, the findings revealed a detection of 172 volatile compounds across the samples, with esters being the most prevalent class, accounting for 42 types. After relative odor activity value (ROAV) analysis, 36 volatile components were identified as significant contributors to the overall aroma. Considerable variations in concentration were identified among the key volatile flavor compounds (1-pentanol (1.21~2.15), caprylic acid (1.51~22.59), ethyl caprate (2.12~14.88), p-anisaldehyde (2.52~4.70), and fennel derivatives (4.61~100)) common to all four Zaolu types. Furthermore, notable differences were observed in other flavor components among the various types of Zaolu. The four Zaolu types were characterized by pronounced salty and umami tastes, with acidity outweighing sweetness and minimal bitterness. However, there were clear distinctions in specific flavor profiles. Compositional analysis of a Zaolu sample revealed protein and polysaccharide contents to be 2.91% and 0.46%, respectively. The amino acid profile was comprehensive, with notable levels of glutamic acid (8.286 mg/mL), serine (3.488 mg/mL), and glycine (3.159 mg/mL). Essential mineral elements, including sodium, calcium, sulfur, iron, and potassium, were detected. In conclusion, Zaolu was found to contain a rich array of flavor compounds with favorable sensory properties, the distinct flavors resulting from different origins and production processes necessitate further research to enhance its development and promotion.